Fenomena Pernikahan dibawah Umur oleh Masyarakat 5.0 - Asep Deni Adnan Bumaeri; Hisam Ahyani; Ahmad Hapidin; Hendi Kusnandar (Mabahits : Jurnal Hukum Keluarga Islam, 2020)
The phenomenon of underage marriage by the 5.0 Society has become a necessity, where one of the economic factors and boredom to study online as it is today during the Covid-19 pandemic has made many 5.0 people in Indonesia apply for early marriage. As a result, the phenomenon of Underage Marriage by Society 5.0 today needs special education for the nation's young people in welcoming a brighter and dignified future according to the demands of the times. The results of the study show that the phenomenon of underage marriage that occurred recently by Society 5.0 is a marriage carried out before the child enters the age of 18 years, this is as stated in Law No. 16 / 2019 About Marriage. Factors that support Society 5.0 to carry out underage marriages include Economic Factors and Factors Tired of learning online, this is because today in an all-digital era like today (the era of disruption 4.0), where people called Society 5.0 feel worried about their inability in competing through artificial intelligence technology so that the concerns of today's society's economic fulfillment are threatened. Constraints faced in the practice of underage marriage by Society 5.0 are from the physical aspect, from the cognitive aspect, the language aspect, the social aspect, and the emotional aspect, where these five aspects cause disharmony and the integrity of marriage in early childhood. The solution in responding to the phenomenon of underage marriage in the 5.0 community is that it can be done through various early prevention by parents, religious leaders, and mass organizations in order to socialize about marriage to the community through the integration of technology that is adapted to the demands of the times, such as online class training for young people, especially those under the age of 18.